(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
Waste management conserves human health, ownership, environment, and keeps valuable natural resources. Lean-green waste of an organization’s operations can be decreased through implementation 3R (Reduce, Reuse, and Recycling) techniques by reduction of manufacturing system wastes. This research aims to integrate lean-green waste of the manufacturing system throughout employing 3R techniques and weighted properties method in order to manage waste. Al-Kufa cement plant is employed as a case study. Results are generated using Edraw Max Version 7 and Excel. Overall results show reduce technique of lean-green waste management has major contribution of 55 % and recycling technique has minor contribution 18 %. Defects waste has major integration of lean-green waste, while air emissions waste has minor integration of lean-green waste.